Personal financial management among university students: the case of Malaysia / Nurul Huda Abd Rahman, Dr. Mohd Nizal Hanif and Norilmiah Azis. - Abd Rahman, Nurul Huda; Hanif, Mohd Nizal (Dr.); Azis, Norilmiah (2008)
This paper investigates the issue of financial management among university students. The objectives of the study are to compare level of financial knowledge of university students according to demographic characteristics, to examine the relationships of self-efficacy and locus of control on financial behavior and knowledge and to examine the relationship of personal financial knowledge on financial behaviour. Questionnaires were sent to university students in Malaysia. The regression results showed individual differences such as self-efficacy, locus of control are significantly related to financial knowledge and financial behaviour. The location of the university and the parents' academic qualification do to a certain extent explain and influence the financial behaviour of respondents. This study provides support on the importance of individual differences in influencing financial knowledge and behaviour among young individuals. They can make better decision when purchasing a product or investment or make borrowing which was consistent with previous studies.